A Pharmacokinetic/Pharmacodynamic Study of Esomeprazole Comparing a Dual Delayed-Release Formulation (YYD601) to a Conventional Formulation Following Multiple Administrations in Healthy Adult Subjects - Lee HW; Kang WY; Park JS; Lee JH; Park JJ; Gwon MR; Yoon YR; Seong SJ (Drug Design, Development and Therapy)
Hae Won Lee,1 Woo Youl Kang,2 Ji Seo Park,1 Jae Hwa Lee,1 Jin Ju Park,1 Mi-Ri Gwon,1 Young-Ran Yoon,1 Sook Jin Seong1 1School of Medicine, Kyungpook National University and Department of Clinical Pharmacology and Therapeutics, Kyungpook National University Hospital, Daegu, 41944, Republic of Korea; 2Clinical Trial Dossier Evaluation Team, Innovative Products Support Department, National Institute of Food and Drug Safety Evaluation, Cheongju, 28159, Republic of KoreaCorrespondence: Young-Ran Yoon, Professor, School of Medicine, Kyungpook National University and Department of Clinical Pharmacology and Therapeutics, Kyungpook National University Hospital, 130 Dongdeok-Ro, Jung-gu, Daegu, 41944, Republic of Korea, Tel +82-53-420-4950, +82-53-420-5218, Email yry@knu.ac.kr Sook Jin Seong, Clinical Associate Professor, School of Medicine, Kyungpook National University and Department of Clinical Pharmacology and Therapeutics, Kyungpook National University Hospital, 130 Dongduk-Ro, Jung-gu, Daegu, 41944, Republic of Korea, Tel +82-53-200-6351, +82-53-420-5218, Email wintersj@knu.ac.krBackground: YYD601 is a new dual delayed-release formulation of esomeprazole, developed to enhance plasma exposure and prolong the duration of acid suppression.Purpose: This study aimed to evaluate the safety, pharmacokinetic (PK), and pharmacodynamic (PD) profiles of YYD601 20 mg following single and multiple oral administrations in healthy, fasting adult Koreans, and to compare these outcomes to those of the conventional esomeprazole 20 mg capsule.Methods: A randomized, open-label, two-period crossover study was conducted in 28 participants, who were divided into two treatment groups: one group received YYD601 20 mg, and the other received conventional esomeprazole 20 mg, once daily for five consecutive days. Blood samples for PK analysis were collected pre-dose and up to 24 hours post-dose. The primary PK parameters (AUClast and AUCτ) were evaluated. PD endpoints included integrated gastric acidity, percentage of time with intragastric pH > 4 over 24-hour and nighttime intervals, and percent change in serum gastrin levels after multiple dosing.Results: A total of 22 participants completed the study. YYD601 displayed more prolonged plasma concentration-time profiles than the conventional formulation, although the extent of the systemic exposure (AUC values) showed no statistically significant difference between the two formulations. With regard to the 24-hour gastric acid inhibition, YYD601 was comparable to the conventional formulation. The YYD601 showed a greater tendency for acid inhibition at night, as indicated by the percentage change of time with nocturnal acid breakthrough and other PD parameters. Both treatments were well tolerated, with no serious adverse events reported.Conclusion: Through extended systemic exposure of esomeprazole, YYD601 produces gastric acid suppression that is comparable to that of the conventional esomeprazole formulation, with a greater tendency to suppress acid at night. YYD601 20 mg was safe and well tolerated following single and multiple oral administrations, supporting its use as an effective alternative to conventional esomeprazole therapy.Clinical Trial Registry: http://clinicaltrials.gov, NCT03985319 (Date of registration: May 29, 2019; Study period: between July 2019 and March 2020).Keywords: esomeprazole, dual delayed-release formulation, pharmacokinetics, pharmacodynamics